Penerapan Pasal 68 Ayat 1 Jo Pasal 4 Dan 6 Undang-Undang No.15 Tahun 2001 Dalam Penyelesaian Sengketa Merek Kok Tong Kopitiam pada Putusan No. 05/Merek/2010/PN.Niaga Medan - Desriyana Desriyana; H.A. Lawali Hasibuan (Universitas Medan Area, 2017)
Application of Article 68 Paragraph 1 Jo Article 4 and 6 of Law No. 15 of 2001 in Brand Dispute Resolution Kok Tong Kopitiam of Decision No. 05 / Merek / 2010 / PN.Niaga MedanAbstractBrands are the result of human thought and intelligence which can take the form of discovery. Brands are used as a differentiator between products produced by a person or legal entity with products produced by other parties. The current journey to free trade, aspects of intellectual property rights, will play a very important role in national and international trade. Intellectual property rights are rights that arise or are born due to human intellectual abilities in the form of findings, works, creations or creations in the field of technology, science, art and literature. Based on Article 68 paragraph (1) of Law Number 15 of 2001 which states that